Prevalence of the reasons for consultation in the Comprehensive Psychology Center of a Colombian University - Berrío-García, Nathaly; Zedán-Salinas, Karina Paola; Benavides-Ponce, Magda Fernanda; Giraldo-Giraldo, Angélica Johana (Pensando Psicología, 2024)
Mental health is a dynamic state, expressed in daily life through the behavior and interaction of an individual and groups, in which the available emotional, cognitive, and mental resources are deployed to live, work, interact and contribute to society. The main objective of this study was to estimate the prevalence of the reasons for consultation of the population of the department of Quindío and the north of the department of Valle del Cauca who attended the Integral Psychology Center of a Colombian higher education institution between 2020 and 2022. The sample consisted of 404 consultants who agreed to participate in the study through informed consent. By gender, the most prevalent reasons for consultation were emotional problems in women (22.4%), and school problems in men (22.4%). The main reason for consultation in children is school problems (37%) and in adolescents it is emotional problems (25.5%). In adulthood, the most common reasons for consultation are marital relationship problems (between 6% and 23.7%), and bereavement (23.5%). The findings suggest the need to plan regional prevalence studies and to carry out a judicious review of public health policies, to include other problems that may be the object of clinical attention as a priority intervention.